A comparative study of myringoplasty versus cortical mastoidectomy with type I tympanoplasty in tubotympanic chronic suppurative otitis media - Sridhar, M. Rama; Sharanam, Shambhavi; Niharika , S. (International Journal of Research in Medical Sciences, 2026)
Background: Chronic suppurative otitis media (CSOM) of the tubotympanic (mucosal) type is a common cause of preventable conductive hearing loss in developing countries. Although myringoplasty remains the standard surgical treatment for dry ears, the role of cortical mastoidectomy combined with type I tympanoplasty in improving anatomical and functional outcomes continues to be debated, particularly in patients with persistent mucosal disease. Objective was to compare the anatomical and audiological outcomes of myringoplasty versus cortical mastoidectomy with type I tympanoplasty in patients with tubotympanic (mucosal) CSOM. Methods: This prospective comparative interventional study was conducted at a tertiary care centre in rural Telangana over an 18-month period. Eighty patients aged 18 to 65 years with tubotympanic CSOM were enrolled and allocated into two groups: group A (myringoplasty, n=40) and group B (cortical mastoidectomy with type I tympanoplasty, n=40). Baseline demographic variables, disease characteristics, and preoperative air-bone gap (ABG) were comparable between groups. Primary outcome measures included graft uptake and postoperative ear status, while secondary outcomes included audiological improvement assessed by ABG closure and hearing gain. Statistical analysis was performed using appropriate parametric and non-parametric tests, with p<0.05 considered statistically significant. Results: The overall graft uptake rate was 92.5% in group A and 97.5% in group B, with no statistically significant difference between the groups (p=0.305). Postoperative ear healing at 3 and 6 months showed similar outcomes in both groups. The mean preoperative ABG was comparable between group A (29.55±5.51 dB) and group B (31.45±5.05 dB). However, group B demonstrated significantly greater audiological improvement, with higher mean ABG closure (24.07±3.28 dB versus 21.45±4.25 dB; p=0.003) and hearing gain (22.07±3.28 dB versus 19.53±4.23 dB; p=0.004). Postoperative complications were infrequent and did not differ significantly between the groups. Conclusions: Both myringoplasty and cortical mastoidectomy with type I tympanoplasty provide high rates of graft uptake and satisfactory postoperative healing in tubotympanic CSOM. However, the addition of cortical mastoidectomy is associated with significantly greater audiological improvement.